Stability of a Structurally Inhomogeneous Flexible Plate in Uniform Axial Flow - Tan, B.; Lucey, Anthony; Pitman, Mark (Ex Ordo, 2012)
This paper considers the hydro-/aero-elastic linear stability of a finite elastic plate held along all four of its edges and subjected to an ideal axial flow. A combination of theoretical and computational modelling is used to frame an eigen-value problem for the fully coupled fluid-structure system. A particular advantage of the method is that it copes readily with structural inhomogeneity. The method is used to predict the behaviour of both homogenous panels and panels to which localized stiffening has been added as a stabilization strategy. Such stiffening is shown to be very effective for the increasing divergence-onset flow speeds and, in the aero-elastic problem, as a means to suppress flutter. Finally, it is shown that two-dimensional analyses are able to provide a close representation of the phenomenology of the full three-dimensional system.